Pengaruh PDRB Per Kapita, Tingkat Pengangguran Terbuka, Indeks Pembangun Manusia, Inflasi, dan Jumlah UMKM Terhadap Potensi Penerimaan Pajak Penghasilan di Kota Medan Tahun 2020-2024 - Sukma Dewi; Haervi Yunira (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the relationship of GDP per Capita, Open Unemployment Rate, Human Development Index, Inflation, and the Number of MSMEs with the potential income tax revenue in Medan City for the period 2020– 2024. The data used are secondary data obtained from the Central Statistics Agency and related institutions. Data analysis was carried out using descriptive statistics, normality test, Pearson correlation test, and graphical analysis with the assistance of SPSS version 25. The results show that simultaneously, the five independent variables have a significant relationship with potential income tax revenue. Partially, GDP per Capita, Open Unemployment Rate, and Human Development Index have a significant relationship with potential income tax revenue, while Inflation and the Number of MSMEs have an insignificant relationship. These findings emphasize that economic growth and human capital quality are important factors in optimizing local tax revenue.